Legal Protection of Personal Data Privacy in the Digital Era: A Comparative Study between Indonesia and ASEAN Countries - Polii, Valentino; Julius, Dian; Banaya, Cristina Looka (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The evolution of digital technology in the ASEAN region poses a considerable hurdle to the path of legal protection of privacy concerning personal data. This study aims to identify similarities in the legal frameworks for personal data protection and their practical enforcement in Indonesia, Singapore, Malaysia, and the Philippines. With the qualitative methodology commending comparative study and content analysis, data were collected from official regulations, literature reviews, and interviews with experts in the field of digital law. The main results showed that the protective systems in Singapore and the Philippines were stronger due to the presence of independent supervisory authorities, enforcement of stringent sanctions, and active civil participation from the public. On the other hand, challenges to enforcement and a lack of civil participation offer Indonesia and Malaysia little hope in softening what may be viewed as structural impediments. The study therefore recommends that for the harmonization of policies in ASEAN, supervisory institutions need to be strengthened, definitions of personal data need to be standardized, and public transparency needs to be enhanced. Particularly, this research is important in that it applies an indicator-based comparative approach and offers actionable policy recommendations that can be adopted regionally, addressing the challenges presented by the new digital era.